Transformational Leadership for the Improvement of Organisational Performance with Organisational Learning and Innovation at a Manufacturing Company - Ahmad Azmy; Yanti Anggraeti (European Management Studies)
Purpose: This study analyses the impact of transformational leadership on organisational performance. Organisational learning and organisational innovation is presented as a link to create improvements in organisational performance in manufacturing companies. Methodology: This quantitative descriptive collected data using survey, with a 5-point likert scale questionnaires. Participants were 121 employees of a company. They were recruited out of a total of 191 employees from all positions in the company. Data were analysed using path analysis with the SEM-PLS method, performed using SmartPLS 3.2.9 software. Findings: The results of the study explain that transformational leadership has an effect on organisational learning and does not have an effect on organisational innovation. Organisational learning has an effect on organisational innovation and organisational performance. Organisational innovation has an effect on organisational performance. Research Limitation: Research is limited to aspects of leadership, organisation and innovation. The research object was carried out at manufacturing companies that require learning and innovation processes as mediation of organisational performance. Originality/Value: The study can serve as a reference for company leaders that transformational leadership style play a significant role in improving organisational performance, and the implementation of organisational learning is crucial to encourage innovation creation.